Productivity comparation of Islamic and conventional banks in Indonesia - Che Mohd Salleh, Marhanum; Rani, Lina Nugraha (Universitas Negeri Surabaya, 2020)
This study aimed to compare the productivity performance of Islamic and Conventional Banks in Indonesia with the Total Factor Productivity Index (TFPCH) indicator. The sample of this study was 14 banks consisting of 7 Islamic Banks and 7 Conventional Banks from 2011-2018. Secondary data were obtained from the annual financial statements of each sample. To measure the total factor productivity index (TFPCH), the Malmquist Productivity Index (MPI) was used as a measure of productivity. It found that the productivity of Conventional Banks was slightly superior compared to Islamic Banks, with contributions from Technical / Technological Change (TECHCH) being the most influential component in the TFPCH composition. Further, there was an indication of a technical increase in both types of banks during the period. The results of this study implied banking industry players to increase their efficiency particularly the usage of technology in providing efficient services to users.